Research on Visual Servo Control of UAV Pod Based on Improved PID Algorithm - Zhao, Mingyang; Yan, Jie; Shi, Dianxi; Wang, Yanzhen; Pan, Jianhen; Du, Jing (Journal of physics. Conference series, 2022)
In view of the traditional PID controller used in the UAV visual servo control, there are problems that the parameter setting is extremely troublesome, and the speed and stability of the system cannot be considered at the same time. An improved PID-based UAV pod visual servo control method is designed. By introducing the concept of integral separation, according to the size of the deviation between the target’s pixel coordinates in the image and the set expected pixel coordinates, it is decided whether the integral control is used or not, which can avoid large overshoot and improve control accuracy. The simulation experiment shows that the visual servo control algorithm based on improved PID has smaller tracking error and higher critical tracking speed than the visual servo control algorithm based on traditional PID, and it has better performance.